2006
DOI: 10.1016/j.ijid.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological features of dientamoebiasis in patients suspected of suffering from a parasitic gastrointestinal illness: A comparison of Dientamoeba fragilis and Giardia lamblia infections

Abstract: D. fragilis and G. lamblia were the most frequently encountered parasites in our study population. Improved diagnostic tests are essential tools to study the prevalence and pathogenesis of D. fragilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
1
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 22 publications
(32 reference statements)
13
72
1
8
Order By: Relevance
“…However, enteric parasites-mainly protozoa-are isolated from 1% to 65% of patients with diarrhea in various settings. The relative prevalences of enteric protozoa reported in several developed countries in outbreak and nonoutbreak settings among humans are reported in Table 1 (1, 11,12,24,60,85,90,96,128,144,184,192,193,204,215,225,247,248,255,264,265,301,335,355,370,395,416,417,425,442,444,452,467). Giardia intestinalis (0.2% to 29.2% of cases), Cryptosporidium spp.…”
Section: Distribution In Developed Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, enteric parasites-mainly protozoa-are isolated from 1% to 65% of patients with diarrhea in various settings. The relative prevalences of enteric protozoa reported in several developed countries in outbreak and nonoutbreak settings among humans are reported in Table 1 (1, 11,12,24,60,85,90,96,128,144,184,192,193,204,215,225,247,248,255,264,265,301,335,355,370,395,416,417,425,442,444,452,467). Giardia intestinalis (0.2% to 29.2% of cases), Cryptosporidium spp.…”
Section: Distribution In Developed Countriesmentioning
confidence: 99%
“…However, high rates of coinfection with other enteric pathogens and protozoa suggest that transmission occurs directly via the fecal-oral route (26,191). Infection may be acute or chronic and has been reported in both children and adults and both immunocompetent and immunosuppressed populations (26,127,361,389,392,444). The most common clinical symptoms include abdominal pain, persistent diarrhea, loss of appetite, weight loss, and flatulence (22,355,389,444).…”
Section: Dientamoeba Fragilismentioning
confidence: 99%
“…Between bouts of diarrhea the patient may have normal stools. However, abdominal discomfort may be continuous and independent of the alteration in bowel habits (271).…”
Section: Giardia Intestinalismentioning
confidence: 99%
“…1,4 Recent studies have shown the organism to be widespread with relatively high prevalence rates ranging from 8.9% to 16.8% in developed regions of the world. [8][9][10] Gastrointestinal symptoms attributed to Dientamoeba infection most commonly include diarrhoea and abdominal pain, with chronic infection often reported.…”
Section: Discussionmentioning
confidence: 99%
“…The parasite has been shown to cause gastrointestinal disease in a wide range of patient groups, has a world-wide distribution and is often more prevalent than Giardia. 1,2 Chronic symptoms have been reported previously in patients presenting with D. fragilis infection. 3 One study found that 32% of D. fragilis infected patients had persistent diarrhoea and associated symptoms of greater than 2 weeks duration.…”
Section: Introductionmentioning
confidence: 86%